AWS CloudFormation master class - Maarek, Stéphane (Packt Publishing, 2018)
"AWS CloudFormation is the best way to write, deploy and maintain your AWS infrastructure. It helps you create efficient solution architectures, all self-contained in one file. It supports most of the AWS services, and is the safest way to make your AWS infrastructure evolve over time. Thanks to YAML, writing AWS CloudFormation templates has become extremely easy and natural. AWS CloudFormation is powerful and supports parameters, mappings, resources, references, cross-stack references, conditions, outputs, metadata, and so much more!"--Resource description page